5PSQ-012 Drug interactions and polypharmacy in a cohort of HIV positive haemophiliac patients. (24th March 2020) - Sanchez-Sancho, P; Gonzalez-Moreno, P; Juarez, JC; Arevalo, AG; Lalueza, P; Ribera, E; Gorgas, MQ
Abstract : Background and importance: The haemophiliac population is getting older and therefore they need to confront other comorbidities in addition to those associated with congenital coagulopathy. Aim and objectives: To determine the complete pharmacological treatment of a cohort of HIV positive haemophiliac patients to determine potential drug interactions (PDI), and to compare them with a reference cohort of haemophiliac patients (RP). Material and methods: A cross sectional observational study was conducted in HIV positive haemophiliac patients, aged over 18 years, and receiving active treatment in February 2019 in a haemophilia unit of a third level hospital. A multidisciplinary team comprising infectious diseases, haematology and pharmacy was established. Biodemographic, clinical and pharmacological variables were recorded. PDI were analysed using the database Micromedex. Moderate and severe PDI were selected. The data were obtained from clinical history (SAP), electronic prescription programme (SILICON) and the electronic prescription system (SIRE). RP was selected from Mannucci et al (2018). Results: The cohort consisted of 40 HIV positive haemophiliac patients with a median age of 49 years (36–75). Clinical variables included type of haemophilia: A (80%), B (5%), factor X deficit (2.5%) and Von Willebrand disease (2.5%). Severity was classified as severe (67%), mild (27.5%) and moderate (5%). Pharmacological variables: recombinant factor (75%: 62.5% extended half-life (EHL) and 37.5% first generation) and plasma derived factor (25%); antiretroviral treatment: tri-therapy (57.5%), bi-therapy (40%), monotherapy (2.5%); total number of drugs (compared with RP): excluding HIV and haemophilia drugs 2.9 (±3.0) versus 2.4 (±2.5), 22.5% had polypharmacy (>5 drugs) versus 17%; including HIV and haemophilia drugs 3.7 (±3.6) versus 4.4 (±3.1), 47.5% had polypharmacy versus 38%. Significant differences were not detected (p>0.05). Thirty-seven PDI were detected and reported (severe 15, moderate 22) which correspond to a rate of 0.6 (±1.4) PDI per patient versus 1 (±2.0) compared with RP (p>0.05). None corresponded to haemophiliac factors. Twenty-four PDI did not require therapy modification, 9 required close monitoring and 4 required an immediate modification to prevent adverse effects on the patient. Conclusion and relevance: Our population had a profile of polypharmacy and PDI similar to another RP. Immediate treatment modification was required in 4 out of 37, indicating the need to actively identify PDI in the HIV positive haemophiliac population. This detection reduces the risk of toxicity or ineffectiveness of antiretroviral therapy. The involvement of the pharmacist in the management of the haemophiliac patient contributes to optimisation of the pharmacotherapeutic plan. References and/or acknowledgements: No conflict of interest.